High hardness cubic boron nitride with nanograin microstructure produced by high‐energy milling. Issue 10 (30th April 2018) - Semenic, Tadej; Hu, Jerry; Kraemer, Stephan; Housley, Robert; Sudre, Olivier
Abstract: High‐energy shaker milling of hexagonal boron nitride (hBN) powders was used to produce powders rich in sp 3 bonding. The powders contained up to 68% sp 3 bonding and were found to nucleate nanosize cBN grains during consolidation at 5.5 GPa and 1400°C. The effect of hBN starting particle size, milling time, and powder‐to‐milling ball ratio were studied. The amount of sp 3 bonding for milled hBN powders was determined, using 11 B solid‐state NMR. The milled material was also analyzed by XRD, Raman spectroscopy, and HRTEM. The results indicate that the material has a nanosized microstructure comprised of a disordered hBN matrix and cBN nuclei in the form of sp 3 ‐rich domains. Eight different milled powders were produced and consolidated at pressures of either 5.5 or 6.5 GPa and temperatures of either 1400°C or 1450°C into 12 mm diameter and 5 mm thick pellets. Consolidated pellets formed from milled hBN with 68% sp 3 bonding had Vickers hardness of 42 ± 1 GPa and fracture toughness 3.8 ± 0.1 MPa.m 1/2 . Vickers hardness of 49 ± 1 GPa and fracture toughness of 4.6 ± 0.1 MPa.m 1/2 was achieved with a precursor that contained milled hBN and 50 vol. % of 0.5 μm diameter cBN crystals.